Geopolitical rifts and the response of ASEAN capital markets and oil & gas issuers to Russia's invasion of Ukraine - Anwar Husni Mubarok; Kelsha Berliana Rifty; Asep Muslihat; Abdul Yusuf (Jurnal STEI Ekonomi, 2026)
This study aims to analyze the response of ASEAN capital markets to Russia’s military invasion of Ukraine, with a particular focus on oil and gas issuers. Using an event study approach, the research examines market reactions to geopolitical shocks and the influence of corporate financial fundamentals on cumulative abnormal returns (CAR). The sample consists of 49 oil and gas companies listed on ASEAN stock exchanges during the 2021–2022 period, selected through purposive sampling. Data were analyzed using paired-samples t-tests and multiple linear regression in Stata 14. The results indicate that ASEAN capital markets generated significant positive CARs during the pre-event and event-day periods, suggesting that investors perceived the increase in global energy prices as a favorable signal for oil and gas companies. In the post-event period, market reactions became more varied, with positive trends continuing in Vietnam, Indonesia, Thailand, the Philippines, and Singapore, while Malaysia experienced negative CARs. Furthermore, regression results reveal that Return on Equity (ROE) has a significant positive effect on CAR, whereas Return on Assets (ROA) has a significant negative effect. This unexpected finding may reflect investor concerns regarding debt exposure and rising interest rates, although these factors were not directly controlled in the model. The study contributes to the literature on geopolitical risk and provides practical insights for investment decision-making and corporate financial management.